Hypertrophic Pachymeningitis in a Southern Chinese Population: A Retrospective Study - Xiao, Xuewen; Fu, Dongni; Feng, Li (Frontiers in Neurology, 2020)
Aims To investigate the causes, clinical characteristics, imaging features and therapeutic implications of HP in a southern Chinese population. Methods We retrospectively analyzed 48 patients with HP with different causes from 1 January 2006 to 31 December 2018. Clinical manifestation, laboratory findings, and neuroimaging results were evaluated in all HP patients. Results The mean age at onset was 50±12 years. The most common diagnosis was idiopathic HP (67%), followed by ANCA-associated vasculitis (15%), tuberculous meningitis (8%), viral meningitis (6%), and bacterial meningitis (4%). Headache was the most common symptom. The most frequently changed laboratory finding was elevated ESR. Imaging was characterized by cerebral or spinal dura matter enhancement in MRI scan with contrast. Enhancements were mainly located in the posterior fossa for idiopathic HP; frontal, parietal and occipital lobes for ANCA-related HP; and the posterior fossa for tuberculous-associated HP. Diffuse enhancement was found in most cases, except for tuberculous-associated HP. Glucocorticoid or immunosuppressive treatment were applied in most cases. Conclusions The etiology of HP varied among patients, with idiopathic HP being the most common. MRI showed enhancement of the dura matter, which differed according to different etiologies. Glucocorticoid or immunosuppressive agents were the primary drugs for treatment.